Perceptions of prospective biology teachers about collaboration in the prospective teacher training program - Ahmad Kamal Sudrajat; Ibrohim; Susilo Herawati; Anggrella Dita Purwinda (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
Collaboration is an important skill for a teacher. Prospective teachers' perceptions about collaboration must be explored to discover their collaboration skills before becoming a teacher. This research aims to determine prospective biology teachers' perceptions regarding collaboration in their teacher preparation program. The study uses a mixed-method approach with an explanatory design. This research uses a survey instrument to obtain quantitative data and semi-structured interviews to obtain qualitative data. A total of 73 prospective biology teacher students were involved in this research. Data were analyzed using a mixed-method approach with explanatory design. The research results show that students have an expert level of collaboration. The gender factor does not significantly influence collaboration, but females have a higher overall score than males. Prospective biology teacher students have been able to define collaboration well, but their definition is not yet in-depth. Prospective biology teacher students have realized the importance of having collaboration skills to support their careers. The recommendation in this research is to develop an appropriate training model to train the collaboration skills of prospective biology teacher students.